PELATIHAN EKSPLORASI PADU PADAN BATIK CAP DAN IKAT CELUP BAGI GURU SMA MATA PELAJARAN SENI BUDAYA - Tridjata, Caecilia; Candrasari, M.C Wara; Hazmi, Fariz Al (Institut Seni Indonesia Surakarta, 2024)
In particular, the quality of learning is determined by a teacher’s abilities. Professional teachers undoubtedly canprovide learning creatively. They must be able to see the situation within the limitations of teaching media needs byutilizing existing resources. Training teachers is essential to improve teachers’ abilities in providing creativelessons to students, especially in creativity-based learning. The Community Empowerment aims to train high schoolteachers in mix-and-match exploration of stamped and tie-dyed batik in arts and culture subjects. The entire seriesof P2M activities are carried out using a Learning-by-doing approach, a demonstration method, and video tutorials.The training takes place in the Betawi pavilion of SMAN 109 South Jakarta. The training results showed thatparticipants were able to complete the entire training series well, even though there were several obstacles. Fromthe results of the work analysis, on average, the participants produced work of excellent quality, so teachers areexpected to be able to teach batik skills to students in their respective schools in arts and culture subjects.